BURUH PEREMPUAN Dl PERKEBUNAN KARET SUMATERA TIMUR1900 -1940 (Women Labour in the Rubber Plantation in East Sumatra 1990 -1940) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This study is aimed to give an explicit description of a woman labour in the rubber plantation at East Sumatra and how was the role of a women as a labour in the process of rubber production in the dutch colonial. This research uses history method, that is heuristic (data collection) source criticism, interpretation (analysis) and historiography. The datas which have been used, based in the research of several colonial files and some others literatures either Indonesia or foreign language. In describing the problems were used the culture and economic approach. The result of this research showes that the women who worked as a labour in the rubber plantation in East Sumatra was caused by the internal and external factor. Internal factor was the effort of the women to support her husband increasing household income for daily needs. Besides, to throw away the perception that women should stay at home and take care the family (domestic), while external factor, related to the industrialization deÂ¬velopment it needs more man powers, so man and woman labour were reÂ¬cruited but the wag es of the women labour is lower than the man labour. The system of women labour recruitment was done by agents, who have been contracted to wok in the plantation, beside that, there was free labours recruitment, who signed the contract as they reached East Sumatra. The process of women labour arrival to East Sumatra was with their family of by their self (especially for the young women).